ANALISIS INPUT-OUTPUT ENERGI BUDIDAYA MENTIMUN (Cucumis sativus L.) DENGAN SISTEM IRIGASI SPRINKLER - Suryanto, Joko; Kasim, Hasni; Nurhayati, Nurhayati (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
The aim of the research was energy analysis (input-output) cucumber in cultivation under sprinkler irrigation system. Data were collected using interview method from cucumber farmer that cultivation cucumber in field 15 x 9 m2 in Bengalon, Kutai Timur. The results indicated that total energy input and total energy output was found 35 204 MJ/ha and 69 926 MJ/ha, respectively. The energy indices covering energy rasio (energy use efficiency), energy specific, energy productivity and net energy were 1,99, 0,40 MJ/kg, 2,48 kg/MJ and 34 722 MJ/ha, respectively. The cucumber cultivativation under sprinkler irrigation system, 38,21 % of total energy input was classified direct energy and 61,79 % was indirect energy. Results futher indicated that 90,18 % of total energy input was in non-renewable energy form, and only 9,82 % was in renewable form. The main non-renewable inputs were fuel and chemical fertilizers 34,53 % and 22, 69 %, respectively. Therefore, irrigation efficiency should be improved and reductions of chemical fertilizers would be suggested to reduce non-renewable energy input in cucumber cultivativation under sprinkler irrigation system. Keywords: Cucumber cultivation, energy rasio, input energy, non-renewable energy, sprinkler irrigation system